Cultural Adaptation, Reliability, And Validity Testing of the Indonesian Version of the Child and Youth Resilience Measure (CYRM) among Islamic Boarding School Students - Ulin Nihayah; Mungin Eddy Wibowo; Dwi Yuwono Puji Sugiharto; Ali Formen (Universitas PGRI Yogyakarta, 2026)
This study aims to culturally adapt and evaluate the Indonesian version of the Child and Adolescent Resilience Measure (CYRM) among boarding school students. The adaptation followed standard guidelines, including forward and backward translation by linguists and expert panel reviews, to ensure cultural and linguistic relevance. A total of 362 students from four Islamic boarding schools in Central Java participated. Reliability testing showed strong internal consistency (Cronbach’s alpha = 0.85) and composite reliability above the ≥0.70 standard. Construct validity was confirmed through exploratory and confirmatory factor analyses, supported by expert judgment on content validity. Model fit indices indicated excellent results (CFI = 0.937, RMSEA = 0.046, SRMR = 0.049). The CYRM structure comprises three dimensions Individual, Relational, and Contextual that capture personal capacity, social support, and cultural context in the face of challenges. Findings demonstrate that the Indonesian CYRM is a reliable and valid tool for measuring resilience, offering culturally appropriate support for research and interventions in Islamic boarding schools. Keywords: resilience, santri, islamic boarding school, child and youth resilience measure (CYRM)